Pengaruh Promosi Jabatan Dan Displin Kerja Terhadap Kinerja Pegawai Pada Kantor Dewan Perwakilan Rakyat Daerah (DPDR) Kota Tangerang Selatan - Komariyah Komariyah; Ali Zaenal Abidin (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
The purpose of this study was to determine the effect of job promotion and work discipline on employee performance at the Regional People's Representative Council (DPRD) office of South Tangerang City. This study used a quantitative method, the sampling technique used slovin sampling, namely 75 respondents. Data analysis used validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, determination coefficient and hypothesis test. The results of this study are Job Promotion has a significant effect on employee performance with a determination result of 57% and the hypothesis test obtained t count> t table or (9.908> 1.993). Work discipline has a significant effect on employee performance with a determination coefficient value of 56.8% and the hypothesis test obtained t count> t table or (9.787> 1.993). Job Promotion and Work Discipline simultaneously have a significant effect on employee performance with a regression equation Y = 14.778 + 0.3331 X1 + 0.316 X2. The coefficient of determination is 63% while the remaining 27% is influenced by other factors. The hypothesis test obtained a calculated F value > F table (61.211 > 2.38).